LESSON STUDY: A QUALITATIVE ANALYSIS USING NVIVO IN CLIMATE CHANGE COURSE - May Yani Br Sembiring; Nova Susanti; Neneng Lestari (Physics and Science Education Journal (PSEJ), 2025)
The research aims to analyze lesson study learning in climate change courses on student collaboration skills during group learning.  The approach used is qualitative with the type of case study. The subjects in this study were physics education students who took climate change courses consisting of 16 students, including 13 female students and 3 male students. Data collection techniques used in the study by means of documentation and observation when learning with lesson study takes place. Documentation data was obtained during the learning process in the form of recordings of discussions of each group that participated in learning in the climate change course. The results showed that the collaboration skills of students varied between groups, influenced by group members and the ability to work together between members. Analysis with TBLA assisted by NVivo through coding and identifying the main themes, from the problems given to discuss related to the issue of climate change and modern agriculture. The results of the analysis based on learners' discussions showed a deep understanding of climate change and suggested solutions, such as vertical farming innovations, to overcome the challenges related to increasingly narrow agricultural land.  This study provides insights into lesson study in improving learners' awareness of climate change issues and learners' collaboration skills. Lesson study, with its collaboration-based approach, enables learners to actively discuss, evaluate and understand the impacts of climate change in a real context.